ANALISA PERANCANGAN SISTEM INFORMASI PENDAFTARAN MAGANG KERJA MENGGUNAKAN WATERFALL - Tb Dedy Fuady; Benny Suhendar (Journal of Innovation And Future Technology (IFTECH), 2020)
The development of technology and communication greatly helps the performance and business processes of an organization. Its development must result in benefits for the organization in obtaining information, as well as assisting the organization in carrying out the required business processes so as to help organizational managers make decisions. Changes in the form of business processes that are used with the development of technology and communication are expected to be able to encourage organizations to have better management. The management of this Field Work Apprenticeship activity still uses manual methods in some of its business processes, so that the benefits of technological developments and communication are not used. Researchers assess and consider the need to develop an information system for Field Work Apprenticeships using the Waterfall method. The test results show that the system is able to carry out the Field Work Apprenticeship business process easily without having to use manual methods such as registering to take part in the Apprenticeship, displaying the information needed in the Apprenticeship activities, manipulating the data used to be used in Internship activities.